Double β Decay and the Axial Strength - Suhonen, Jouni; Kostensalo, Joel (Frontiers in Physics, 2019)
Quenching of the weak axial strength g_A is discussed and relations of this quenching to the nuclear matrix elements of double beta decays are highlighted. An analysis of Gamow-Teller transitions in the mass range A=62-142 is presented and its results are compared with those of many previous works. The enhancement of the axial charge is discussed for first-forbidden pseudoscalar beta transitions. Higher-forbidden beta transitions are introduced and their role in determining the effective value of g_A is examined, in particular from the point of view of rge beta-decay half-lives and the shapes of electron spectra of forbidden non-unique beta transitions.